REHABILITATING HUMAN NATURE - Andreou, Chrisoula (Bioethics, 2010)
I review the main models of disability and introduce a line of reasoning that has been neglected in the debate concerning disability and disadvantage. My reasoning suggests that while disablism can and should be combated, success will require more challenging transformations than those featured in the literature.